2014
DOI: 10.1021/pr500635f
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive and Scalable Highly Automated MS-Based Proteomic Workflow for Clinical Biomarker Discovery in Human Plasma

Abstract: Over the past decade, mass spectrometric performance has greatly improved in terms of sensitivity, dynamic range, and speed. By contrast, only limited progress has been accomplished with regard to automation, throughput, and robustness of the proteomic sample preparation process upstream of mass spectrometry. The present work delivers an optimized analysis of human plasma samples in both small preclinical and large clinical studies, enabled by the development of a highly automated quantitative proteomic workfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(102 citation statements)
references
References 28 publications
4
97
1
Order By: Relevance
“…are performed. Dayon et al demonstrated the scalability of depletion, TMT labeling and ESI analysis, with cited a throughput of 2 × 96 samples in 3 weeks and 1005 samples in 15 weeks . Such measurements would allow plasma proteomics to catch up to some degree with genomics measurements.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…are performed. Dayon et al demonstrated the scalability of depletion, TMT labeling and ESI analysis, with cited a throughput of 2 × 96 samples in 3 weeks and 1005 samples in 15 weeks . Such measurements would allow plasma proteomics to catch up to some degree with genomics measurements.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Using samples collected from a large study cohort, Cominetti et al analyzed in the order of 1000 plasma samples from 525 individuals enrolled in a study related to diet, obesity and genetics (DiOGenes project) . Using a semi‐automated platform and work flow (presented in an earlier publication by Dayon et al ( vide supra ), a total of 1005 samples were analyzed. They observed that CRP and S100A9 were correlated with BMI and that pregnancy zone protein (PZP), SHBG and APOC‐II provided potential gender discrimination.…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…This unfortunate tradeoff between depth and throughput has meant that studies in plasma proteomics that include relatively large numbers of samples (many tens to >100) typically have shallow depth of coverage (e.g., Cominetti et al 17 and Dayon et al 18 ), whereas studies emphasizing depth of coverage typically have small sample numbers (e.g., refs. 1921 ).…”
Section: Introductionmentioning
confidence: 99%
“…After the depletion of six abundant proteins, Cole et al performed 8-plex iTRAQ labeling and SCX separation into 24 fractions, resulting in the quantification of ~900 proteins across 500 patient plasma samples spanning 72 iTRAQ experiments 34 . In the largest patient study yet reported, Cominetti et al applied an automated plasma processing workflow that included depletion of 14 abundant proteins, 6-plex TMT peptide labeling and online LC–MS/MS analysis without fractionation to >1,000 patient samples 17,18 . Although each sample required only 3 h of instrument time, this study identified only 365 proteins in total across all samples.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Incorporating the automated solutions in proteomics high throughput sample preparation needs to be tailored to the specific workflow and has to be determined by the number of samples, the size and type of these samples, experimental protocols applied, and instruments available in the laboratory [15]. It is problematic to establish a fully automated protocol in extensive and elaborate proteomics workflows due to all the variables in the multiple often disjointed sample preparation steps.…”
mentioning
confidence: 99%